Use of calcium carbide for gold recovery from arsenic refractory minerals - Shishido Sánchez, Manuel (2017)
The arsenopyrite, FeAsS, it is a mineral that is commonly found associated with gold. In this kind of mineral, Gold is presented in sub-microscopic size particles, encapsulated in a matrix of the same mineral or forming a solid solution, this does not allow the recovery of gold with the available lixiviation techniques. Moreover, a fine grinding does not a chive to break the matrix in which the gold is located, not allowing the lixiviation solutions to come in. Some alternatives that lead to the recovery of gold from those minerals include chemical oxidation, oxidation under pressure, bacterial oxidation and roasting oxidation (which is very polluting due to the emission of As2O3 y SO2 gases. The aim of the following study is to identify the conditions to break the arsenopyrite matrix for continuing the usual process of cianuration. For doing so, experiments were carried out containing arsenopyrite with gold contents.